Elements of Social Responsibility in Clusters - Anna Horzela (Journal of Management Practices, Humanities and Social Sciences, 2019)
The aim of the research work is to identify the existing strategies of selected clusters and develop recommendations for taking into account the principles of Corporate Social Responsibility (CSR) in cluster operations. CSR gains these days more and more attention. It is connected with the activity that includes the ethical conduct of the organization towards the public, in particular its recipients, employees, other stakeholders as well as the impact on the natural environment. One of the main barriers to the development of cages is the lack of mutual trust. The literature of the subject and the opinions of practitioners indicate trust as a key factor in the success of cluster initiatives. For this reason, creating an environment friendly to its construction should be one of the first steps taken by cluster participants. Considerations about the role of trust in the cluster's construction process and the related barriers to cluster development result in the thesis that one of the obstacles to the cluster's activity is the lack of faith that its participants will behave in a socially responsible way. In addition, the progressing promotion of CSR is playing an increasingly important role in stimulating the emergence and development of cooperative relationships such as clusters. The work includes the collection, processing and analysis of data, information and knowledge necessary to develop final conclusions. In the research, qualitative and quantitative methods as well as literature analysis from the studied area is used. The work takes into account cluster strategies in which elements of CSR are identified. The findings aim to contribute in building recommendations for the implementation of the principles of CSR in the activities of clusters.